Olympic Games and Territory Conflicts and tensions between emotion and representation in Rio 2016 (Huellas, 2017)
Mega sports events (Olympic Games, Winter Olympic Games, Soccer World Cup, Formula One World Championship, among others) constitute a phenomenon proper of capitalism, and the geographical space occupied for those events is by no means a passive scenario which merely contains them. On the contrary, it plays a crucial role in the construction of territories filled with specific infrastructure, symbolism and competitiveness. The territorialization of those mega events is an expression of political, economic and cultural interests. Although their duration is ephemeral, they produce a significant impact at local, regional and global scales.Countries and cities which apply to be hosts, compete in order to obtain greater visibility, improve their urban infrastructure, attract tourism and, as a result, to obtain a territorial projection at both regional and global scales.In this article, the Olympic Games held at Rio 2016 are approached in order to analyze the territorial impact and its projection in the global scenario. The magic and emotion of the Olympic Games were not able to hide certain emerging problems, and thus, our idea is to mention some of them and show how the sports event was turned into a platform from which to place them in the world mass media. Our methodology consisted in a critical analysis of secondary sources and their articulation with key concepts of Geography to analyze the territorial impact of such a mega event as Rio 2016 from a geo-economic and geo-strategic perspective, but also to examine the social significance of the everyday life of different subjects who live in these territories amidst tensions and conflicts.
Keywords: Geography; Territory; Olympic Games; Territorial problems.